TANTANGAN DALAM DIAGNOSIS DAN MANAJEMEN PADA KEHAMILAN DENGAN THALASSEMIA MAJOR: LAPORAN KASUS - Layarta, Crismanto; Prijatna, Arief; Widyastuti, Ratna (Biomedika, 2019)
Thalassemia (including one type of haemoglobinopathies) is the most common genetic disease in the world. Pregnancy with thalassemia major is at risks of fetal hypoxia, intrauterine growth restriction, and prematurity as twice as normal pregnancy. We report a case of pregnancy, 28-years-old pregnant woman, in poorly treated thalassemia major patient. She came to obstetric outpatient clinic for the first antenatal care. Her gestational age was 19-20 weeks. She was diagnosed with thalassemia major previously, with poorly treated. She was pale and her spleen was enlarged with Schuffner score amounted to four. Her face showed Cooley facies which is specified in thalassemia patient. Her initial hemoglobin level was 2.2 g/dL with hypochromic microcytic erythrocyte. Thereafter, she underwent 4 series of packed red cell transfusion until delivery. The electrocardiography showed left ventricular hypertrophy with global ischemia. The pregnancy was terminated by elective caesarean section by indication of cephalopelvic disproportion. There was no intrapartum and postpartum complication in this patient. Her baby was 2,800 grams and 47 cm in length. Hereinafter, no abnormalities were found in neonatal examination. This case emphasizes the importance of establishing a diagnosis and the optimal treatment op of thalassemia major during pregnancy. Collaboration of obstetrician, cardiologist, hematologist, and neonatologist is needed to attain favorable pregnancy outcome in thalassemia major pregnant patients.Keywords: Thalassemia Major, Pregnancy, Outcome